Sarcoidosis Incidentally Diagnosed: A Case Report. (7th July 2014) - Kesici, Besir; Toros, Ahmet Burak; Bayraktar, Levent; Dervisoglu, Adem
Abstract : Sarcoidosis is a chronic, granulomatous condition with unknown cause. Because most of the patients are free of clinical symptoms, sarcoidosis should be considered in differential diagnosis if noncaseous granuloma is noted in biopsies, performed for other reasons. With no clinical symptoms, our patient was diagnosed with sarcoidosis upon identifying noncaseous granuloma in the lymph node biopsy material collected during the laparoscopic operation, performed for gallbladder polyp.